Diagnosis and therapy of parathyroid cysts: A review of 7 cases - Zhiwei Zhou; Jingjia Li; Weixiong Chen (Acta Oto-Laryngologica Case Reports)
Parathyroid cysts (PC) are relatively rare lesions in the neck. This study aims to present 7 new cases of PC and share our experience. Between September 2017 and December 2022, seven patients diagnosed with PCs underwent surgery. Relevant clinical data were collected. Five of the patients had non-functioning parathyroid cysts (NPC) and the remaining two had functioning parathyroid cysts (FPC). Cystic fluid contained high level of parathyroid hormone (PTH). Histologically, NPCs were confirmed as true parathyroid cysts, while FPCs were attributed to cystic degeneration of parathyroid adenomas. Three cases showing elevated PTH level following surgery, however, it subsequently returned to normal in all these cases. No recurrence or abnormal calcium levels were reported during follow-up. In conclusion, PTH level in cystic fluid can aid in the diagnosis of PC. It is important to differentiate between NPC and FPC. Surgical excision is preferable for both types.